PREVALENCE OF HYPERALDOSTERONISM AMONG PATIENTS WITH SECONDARY ARTERIAL HYPERTENSION - Поддубная, Антонина; Гончарук, Людмила; Садовий, Костянтин; Гузун, Денис; Охота, Анна (Modern engineering and innovative technologies, 2023)
Hyperaldosteronism is a complicated symptom complex, one of the manifestations of which is persistent arterial hypertension. In 15% of patients with arterial hypertension, the cause is hyperaldosteronism. The only effective method of treating arterial hyp